QUALITY AND RELIABILITY, PRICE, COMMUNICATION AND POWER FACILITIES AS PREDICTORS OF HOUSEHOLD SATISFACTION TO POWER UTILITY SERVICES - Himang, Celbert M (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
The Central Visayas Region in the Philippines envisions being the center of tourism, trade and industry. Thus, this study investigated the relationship between household overall satisfaction to power utility services in Cebu City and satisfaction attributes. A researcherdeveloped questionnaire was used for this household survey research to gather data from 377 households of the 50 urban Barangays in Cebu City, Philippines. Statistics used were percentages, means, and standard deviations, multiple linear regression and analysis of variance. Thirteen attributes (power quality and reliability, billing and payment, corporate citizenship, price, communication, customer service-staff, customer service-paying center, customer service-power facilities, kilowatt-hour consumed per month, amount due, educational attainment, age and number of household members) were assessed out of which only four (4) attributes showed a significant relationship with household overall satisfaction. No significant difference was found on the level of overall satisfaction among households on the cluster membership based on demographic variables. It was concluded that household customer satisfaction is not dependent on socio-economic status but is significantly related with quality, price, communication and power facilities of the power utility services. Other utility services satisfaction can be simultaneously done for a comprehensive view on the part of tourists, and the trade and industry sectors.